INFLUENCE OF WEATHER PARAMETERS ON SUCROSE ACCUMULATION IN SUGARCANE (SACCHARUM OFFICINARUM L.) - D, ADILAKSHMI (The Journal of Research ANGRAU, 2026)
The ripening of sugarcane is largely influenced by weather factors such as sunlight, temperature, and rainfall. This study evaluated ten sugarcane clones over two crop years (2023 24 and 2024–25) under the agro-climatic conditions of Andhra Pradesh, India, to assess the effect of weather parameters on sucrose accumulation. The clones were observed from October to February and data on sucrose percentage and weather elements (maximum and minimum temperature, rainfall, and bright sunshine hours (BSSH)) were collected. Correlation analysis revealed that BSSH had a strong positive correlation (r = 0.75) with mean sucrose, followed by minimum temperature (r = 0.54), while rainfall showed a negative correlation (r = –0.68). These results affirm the critical role of incident sunlight and cold weather in enhancing ripening. Clones 2022A 93, 2022A 203, and 2022A 88 demonstrated superior performance across seasons and can be considered for further line development or trait introgression breeding.